2017
DOI: 10.1016/j.apmr.2016.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Multifidi Muscle Characteristics and Physical Function Among Older Adults With and Without Chronic Low Back Pain

Abstract: Objective The purpose of this study was to determine if multifidi size and/or intramuscular fat were associated with self-reported and performance-based physical function in older adults with and without chronic LBP. Design Case-control study Setting Individuals participated in a standardized evaluation in a clinical laboratory and underwent magnetic resonance imaging (MRI) of the lumbar spine at a nearby facility. Patient Sample A volunteer sample of 106 community-dwelling older adults, aged 60-85 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 44 publications
3
35
0
Order By: Relevance
“…An increasing body of research supports the "cLBPdriven early muscle aging" theory, including back imaging studies that observed a loss in muscle cross-sectional area (a suggested indicator of force production capacity (Lieber and Bodine-Fowler 1993)), and increased intramuscular fat replacement (Dahlqvist et al 2017;Goubert et al 2016;Mannion et al 1998;Sions et al 2017b) (fat replacement is indicative of aging and pathology (Hebert et al 2014)). However, such age-and pain-related magnet resonance imaging (MRI) diagnosed muscle morphological alterations were of limited predictive value when related to the degree of disablement (Sions et al 2017a;Suri et al 2015). By contrast, observations of divergent alterations in muscle fiber distribution within the back extensors of older individuals and individuals with cLBP widely refute such a theory.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing body of research supports the "cLBPdriven early muscle aging" theory, including back imaging studies that observed a loss in muscle cross-sectional area (a suggested indicator of force production capacity (Lieber and Bodine-Fowler 1993)), and increased intramuscular fat replacement (Dahlqvist et al 2017;Goubert et al 2016;Mannion et al 1998;Sions et al 2017b) (fat replacement is indicative of aging and pathology (Hebert et al 2014)). However, such age-and pain-related magnet resonance imaging (MRI) diagnosed muscle morphological alterations were of limited predictive value when related to the degree of disablement (Sions et al 2017a;Suri et al 2015). By contrast, observations of divergent alterations in muscle fiber distribution within the back extensors of older individuals and individuals with cLBP widely refute such a theory.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we did not evaluate the severity of the clinical symptoms correlated with atrophy or fatty infiltration of the paraspinal muscles. However, the fatty infiltration of the multifidus muscle correlated with self-reported disability, 34 influenced the physical function of the patients with chronic low back pain, 5 and decreased range of motion during lumbar flexion. 35 Fatty infiltration of the multifidus muscle, longissimus muscle, and iliocostalis muscle was found in the patients with continuous chronic low back pain rather than in the patients with recurrent or noncontinuous chronic low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…4 Fatty infiltration of the multifidus muscle at the L5 level influenced physical function among older adults with chronic low back pain. 5 The extent of atrophy of, and increased fat infiltration into, the lumbar paraspinal muscles of patients with lumbar problems such as back pain, lumbar radiculopathy, or degenerative lumbar kyphosis remains controversial. However, to the best of our knowledge, only three reviews on atrophy and fat infiltration of the lumbar paraspinal muscles in patients with back pain have been described.…”
Section: Introductionmentioning
confidence: 99%
“…When the spine suddenly becomes imbalanced, the MF would contract before the larger muscle groups adjust the displacement of individual vertebral segments. MF is a fundamental part to maintaining the normal biometric lines of the spine and enhancing lumbar stability [31,32] . ES covers the lumbar and thoracic region; it is a large muscle group that maintains the stability of the spine.…”
Section: Effect Of Different Exercises On Lumbar-abdominal Muscle Actmentioning
confidence: 99%
“…ES covers the lumbar and thoracic region; it is a large muscle group that maintains the stability of the spine. ES is a primary muscle for plank; both sides of ES contract to resist body gravity and keep the spine in a stable condition [32] . Previous studies showed that side stay and bridge exercises are good for back muscles, such as MF and ES, in WBV condition [20] .…”
Section: Effect Of Different Exercises On Lumbar-abdominal Muscle Actmentioning
confidence: 99%